Knowledge, attitude, and practice regarding COVID-19 among doctors of Janakpur, Nepal - Jha, Shailesh Kumar; Jha, Rani; Jha, Nikhilesh (Janaki Medical College Journal of Medical Science, 2021)
Background and Objectives: COVID-19 is a global pandemic. Practicing hand and respiratory hygiene is important at all times and is the best way to protect others and oneself from COVID-19. People’s behavior plays important role in control of any infectious disease. Knowledge, attitude and practices (KAP) of a person determines the adherence to the control measures. As doctors are the frontline warriors in this pandemic, an online survey as conducted among the doctors of Janakpur for the assessment of their knowledge, attitude and practice regarding COVID-19. Material and Methods: This study is a cross-sectional online survey using self-administered Questionnaire designed after proper literature survey. The survey was conducted from 4th August, 2020 to 20th August, 2020. Results: Overall knowledge about the various aspects of COVID-19 among the doctors of Janakpur was 81.25%. A positive attitude was noted among 78.12% of the respondents. However, majority (90.6%) of the doctors thought that the country is not prepared to handle the pandemic. Good practice to prevent and treat COVID-19 was shown by 84.37% of the doctors. Conclusion: Doctors of Janakpur show good knowledge, a positive attitude and good practice on various aspects of COVID-19. A significant positive correlation exists between knowledge, attitude and practice among them.